Survival and Growth of Sumatran Featherback (Chitala hypselonotus, Bleeker 1852) Reared on Net Cages - Muslim Muslim; Alharis Ramadhan (College of Vocational Studies, Bogor Agricultural University, 2025)
The Sumatran featherback (Chitala hypselonotus, Bleeker 1852) is a high-value freshwater fish species in South Sumatra. The local name for this species is belida or belido. In its natural habitat, the population of this species has declined. The objective of this study was to evaluate the survival, growth, and feed efficiency of C. hypselonotus reared in net cages. This study was conducted from June to August of 2024 in Putak River, Putak Village, Gelumbang District, Muara Enim Regency. C. hypselonotus was reared in net cages (1x1x1 m) for 30 days and fed with live shrimp (Caridina sp.). The experimental method utilizes a comparative study approach. The present study compared two distinct treatments, each with a feeding rate of 3% and 5%, respectively. Each treatment was repeated three times. The data were tabulated with the assistance of the Microsoft Excel 2020 program and subsequently analyzed using the t-test. The results demonstrated that the survival rate of C. hypselonotus was 100% for both treatments. Growth in body weight and total length in the 5% treatment was superior to that of the 3% treatment; however, the t-test results were not significant (P < 0.05). The results of this study provide a starting point for future investigations.